PERBANDINGAN ANTARA KADAR KALIUM SERUM DENGAN ATAU TANPA TERAPI INSULIN PADA PASIEN DIABETES MELLITUS TIPE 2 - Andi Syamsudduha; S. V Sembiring; R DN Pakasi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Diabetic patients can suffer from hipokalemia because of prolonged osmotic diuretic and management diabetic mellitus with insulinif does not associate with kalium intake. The aimed of this study was to evaluate kalium serum level on type 2 DM, and comparisonof kalium serum level on type 2 DM patients with or without insulin therapy. A cross-sectional study was done on 33 patiens type 2diabetic mellitus that admission on Stella Maris Hospital who examined kalium serum level. The data were colected from Medical Recordperiode January to December 2007. Data were analyzed with Fisher Exact test using SPSS versi 11.5. From 33 samples found normalkalium level 9 samples (27.3%) and decreased 6 samples (18.2%) and without insulin therapy found decresed 3 samples (9.1%) andnormal Kalium level 15 samples (45.5%). Comparison of Kalium serum level of type 2 DM patiens with or without insulin therapydid not statistically significant with P = 0.135. Kalium serum level of type 2 DM patiens with or without insulin therapy commonly inreference value.